PENGARUH PENGGUNAAN MODEL EXAMPLES NON EXAMPLES TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SDN SIAYUH KECAMATAN KELUMPANG BARAT KABUPATEN KOTABARU (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
ABSTRACTThe learning of writing skills at the elementary level is the basis for the higher level later butin general writing skills in elementary school students is still low for it need special learningfor students to increase their writing skills, one of the learning models for it can be used modelexamples non examples, for that from this research is known influence of usage of modelexamples non examplesterhadap skill writing skill of narration at student of class V SDNSiayuh Kecamatan Kelumpang Barat Regency Kotabaru.This research is in the form of class research because it cooperates with classroom teacher toconduct research activities in class by comparing between learning model of lecture withmodel examples non examples.The results showed that the application of examples non examples model in the process ofwriting narrative writing can improve the students' writing skill from the previous gradeaverage score of 60 to 88.58 or an increase of 38.43% so that this model is very effective usedby teachers Indonesian and Indonesian Literature if they have problems writing skills to theirstudents.Keywords: Writing Skill, Model Examples Non Examples